Electrospun Sn-doped TiO2: Synthesis, structural, optical and catalytic performance as a function of Sn loading and calcination temperatures. Issue 7 (1st April 2023) - Pascariu, Petronela; Cojocaru, Corneliu; Homocianu, Mihaela; Samoila, Petrisor; Romanitan, Cosmin; Nikolay, Djourelov
Abstract: A series of tin (Sn)-doped titania (TiO2 ) composites were prepared by electrospinning and then calcined at temperatures of 500 °C, 600 °C, and 700 °C. The morpho-structural and optical properties of the resulting composites were assesed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), diffuse reflectance spectroscopy (DRS), and photoluminescence (PL) spectroscopy. In this way, the effect of the dopant amounts and calcination temperatures on the composition, morphology, band gap energy ( E g ) of the prepared composites was established, as well as their photocatalytic activity towards ciprofloxacin (CIP) photodegradation. The kinetics of ciprofloxacin photodecomposition reactions was analyzed. Herein, it is reported that the nanostructured material based on ([1.5%]Sn:TiO2 ) sintered at 500 °C shows a remarkable photocatalytic activity with a removal efficiency of about 100% and a rate constant of 9.685 × 10 −2 min −1 . The photocatalytic stability of this material was evaluated by reusability tests with five cycles under identical conditions for CIP photodegradation. In-depth structural investigations were undertaken to explain this remarkable photocatalytic activity towards water decontamination.